Self-Reported Effectiveness of e-Learning Classes during COVID-19 Pandemic: A Nation-Wide Survey of Pakistani Undergraduate Dentistry Students - Sarwar, Huma; Akhtar, Hira; Naeem, Meshal Muhammad; Khan, Javeria Ali; Waraich, Khadija; Shabbir, Sumaiya; Hasan, Arshad; Khurshid, Zohaib (European Journal of Dentistry, 2020)
Objectives The main aim of this study was to determine the undergraduate dental students’ self-reported effectiveness of online classes offered by various dental institutes of Pakistan.Materials and Methods A cross-sectional study was conducted using an online survey. A pretested and validated questionnaire comprising of 31 questions was circulated among dental students. The study participants were inquired about the perceived level of accessibility of resources and the effectiveness of online teaching. The data was analyzed using SPSS version 24. Mann–Whitney U test and Kruskal–Wallis test were used for statistical analysis at p ≤0.05.Results A total of 1,207 students from all over Pakistan responded. The majority of students was dissatisfied with the institutional learning management system and quality of learning resources available. Students were also dissatisfied with the level of training of teachers for online lectures. The worst rating was reported for questions related to the effectiveness of online classes (average rating: 3.83 and 3.781/5). First-year students reported poor interaction with teachers (p < 0.001) and strongly disagreed with the effectiveness of online classes (mean rating: 4.14 ± 0.935).Conclusions The results from the present survey showed that dental students of Pakistan unanimously voiced dissatisfaction toward various elements of online teaching sessions. Findings from this survey will aid the academic institutes to establish proficient learning platforms focused on improving students` learning experience.
Keywords: dental students; e-learning; COVID-19; dentistry; online teaching; dental education